POSITIVE FUNCTION OF CONFLICT ON THE MAIN CHARACTER IN THE MOVIE AMADEUS (1984) - Gilang Pamungkas (Universitas Pakuan, 2021)
The topic of this article is positive function of conflict on the main character in the movie Amadeus (1984). Conflicts are part and parcel of life. Not only human, but all living beings experience conflict at one or other point in their lives. Conflict that is managed and expressed properly is called a positive function which influences the pragmatic conflict sociology, or multidisciplinary sociology, that was used to manage conflict in companies or other modern organizations. The study of the main character in this paper uses the conflict theory according to Coser which states that there are two types of conflict, namely realistic and non-realistic conflicts. It can be seen how Salieri, the main character, continues to struggle by trying to improve his composition skills. Despite being faced with absolute power, his love for music did not stop him from fighting. With Salieri's position as Mozart’s superior, Mozart brought out all the talents he had in order to survive and go hand in hand with the circumstances at that time to be able to produce brilliant works from the two composers. This is a sign that conflict does not always have a negative function but can also be a positive function.Keywords : Main Character; Conflict; Positive; Function